Violence Against Women and Children, Vol 1: Mapping the Terrain. 2011
DOI: 10.1037/12307-009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of domestic violence.

Abstract: The World Health Organization (WHO; 2002) referred to violence as a "universal scourge that tears at the fabric of communities" (p. 1). Violence against women by intimate partners-often called domestic violence (DV), intimate partner violence, or wife battering-accounts for a major portion of the violence that occurs worldwide. The definition of DV itself has been the focus of debate and scholarship. The American Psychological Association (1996) defines domestic violence as the range of physical, sexual, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…These women are often classified as "white," obscuring issues related to ethnicity and immigration status. Related to these problems is that some common types of abuse directed at immigrant and refugee women, such as using immigration status as a method of coercive control, are not measured in mainstream surveys or by widely used violence measures such as Straus, Hamby, BoneyMcCoy & Sugarman's (1996) revised Conflict Tactics Scale (CTS) (Dutton, Orloff & Hass 2000;Perilla et al 2011). Likewise, national studies may mask important local factors determining victimization rates, pointing to the need for community-specific studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These women are often classified as "white," obscuring issues related to ethnicity and immigration status. Related to these problems is that some common types of abuse directed at immigrant and refugee women, such as using immigration status as a method of coercive control, are not measured in mainstream surveys or by widely used violence measures such as Straus, Hamby, BoneyMcCoy & Sugarman's (1996) revised Conflict Tactics Scale (CTS) (Dutton, Orloff & Hass 2000;Perilla et al 2011). Likewise, national studies may mask important local factors determining victimization rates, pointing to the need for community-specific studies.…”
Section: Resultsmentioning
confidence: 99%
“…The next step is to examine how much of the variation in violence against women among people of different racial/ethnic backgrounds can be explained by socio-demographic, environmental, and other factors (Perilla et al 2011;Tjaden & Thoennes 2000), which is beyond the scope of the research reported here.…”
Section: Race/ethnicitymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, domestic violence consists of physical, sexual, psychological and controlling behaviour against an intimate partner (Esquivel-Santoveña, Lambert and Hamel, 2013). Very specifically, domestic violence or violence that takes place at home accounts for a major portion of the violence that occurs worldwide against women (Perillia, Lippy, Rosales, and Serrata, 2011). Specifically, domestic violence which is perpetrated by the husband cuts across socio-economic, religious, and ethnic boarders (Richardson, Coid, Petruckevitch, Chung, Moorey, and Feder, 2002).…”
Section: Introductionmentioning
confidence: 99%